Faktor-Faktor Yang Berhubungan dengan Perilaku Pencegahan Obesitas pada Siswa-Siswi SMAI Panglima Besar Soedirman 1 Bekasi dan Tinjauannya Menurut Pandangan Islam - Rahmawati, Kus Fanisa; Rifqatussa’adah, Rifqatussa’adah; Arsyad, Arsyad; Sari, Siti Maulidya; Arifandi, Firman (Syntax Literate, 2026)
Obesity among adolescents is a growing public health problem that can have long-term impacts on quality of life. This study aimed to identify factors associated with obesity prevention behavior among students of SMAI Panglima Besar Soedirman 1 Bekasi and to review these factors from an Islamic perspective. This study employed a quantitative method with a cross-sectional design. The study population consisted of tenth- and eleventh-grade students, with a total sample of 220 respondents selected using proportionate stratified random sampling. Data were collected through a questionnaire that had been tested for validity and reliability, and were analyzed using the Chi-Square test. The results showed that the majority of respondents demonstrated good obesity prevention behavior (53.2%). Bivariate analysis indicated significant associations between obesity prevention behavior and family history of disease (p = 0.046), knowledge (p = 0.017), attitude (p = 0.021), dietary patterns (p = 0.040), peer support (p = 0.008), school facilities (p = 0.034), and the use of information technology for body weight monitoring (p = 0.011). Social support and the utilization of technology were found to play important roles in encouraging healthy behaviors among adolescents. In conclusion, obesity prevention behavior is influenced by individual, social, environmental, and technological factors. From an Islamic perspective, obesity prevention aligns with the teachings of balance, avoiding excess in eating and drinking, and maintaining health as a trust from Allah SWT.